Integrated strategy for PET recycling: Efficient production of H2 and BTX from PET waste via aqueous phase reforming and subsequent catalytic hydrodeoxygenation - Murali, Vishnu; Kim, Hanbyeol; Kim, Jichan; Kim, Eunseo; Park, Young-Kwon; Ha, Jeong-Myeong; Kim, Jungrae; Vlachos, Dionisios G.; Jae, Jungho (Elsevier, 2025)
Polyethylene terephthalate (PET) waste represents an abundant and underutilized resource for producing valuable chemicals and fuels due to its rich aromatic rings and ethylene glycol (EG) units. In this study, we present a novel integrated strategy for converting PET into hydrogen and high-value aromatics-benzene, toluene, and xylenes (BTX)-through aqueous-phase reforming (APR) and subsequent hydrodeoxygenation (HDO). Hydrogen production from PET is achieved through APR reactions over Raney (R) Ni and oxyphilic support-loaded Ru catalysts. Simultaneously, high-density BTX hydrocarbons are synthesized via a single-step process over Ru/ZnO catalysts in a biphasic system. Our findings reveal that Ru nanoparticles dispersed on ZnO serve as an effective catalyst for the low-temperature (220 degrees C) reforming of EG derived from PET, achieving a yield of 7.6 mol/kg (PET). Furthermore, the process efficiently converts PET waste into high-purity terephthalic acid (TPA) with a yield of 74.6 %. For TPA HDO, Ru/ZnO proves to be highly effective for hydrogenolytic conversion of TPA aromatic rings in a biphasic medium. Under mild conditions (220 degrees C, 5 bar H-2, 8 h), the Ru/ZnO catalyst achieves gasoline-range BTX aromatics with a high selectivity of similar to 99.8 %. Overall, this integrated approach offers a sustainable solution for efficiently converting PET waste into valuable products, including hydrogen, high-purity TPA, and BTX. This strategy contributes to circular economy development, addresses plastic pollution, and reduces the carbon footprint associated with PET waste.